Inovasi Pendidikan Mulalui Kurikulum Merdeka: Upaya Meningkatkan Keterampilan Siswa di Abad ke-21 - Riri Fratiwi Iyanda; Reva Kurnia Dewita; Riski Apriyanti; Merika Setiawati; Hendri Budi Utama (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to explore educational innovation through the implementation of the Merdeka Curriculum as an adaptive strategy to enhance 21st-century skills among Indonesian students. Employing a qualitative research method with a literature review approach, this research synthesizes a range of scholarly sources, including journal articles, research reports, and educational policy documents published within the last decade. The findings reveal that the Merdeka Curriculum emerges as a response to the urgent need for a more flexible, student-centered learning system that emphasizes the development of critical thinking, creativity, collaboration, and digital literacy. In the context of an increasingly dynamic global landscape, this curriculum provides educators with the space to innovate through differentiated instruction, projectbased learning, and the strengthening of students' character aligned with the Pancasila Student Profile. However, several implementation challenges persist, including teacher readiness, infrastructural disparities, and unequal access across regions. Therefore, continuous policy support and teacher capacity building are essential to fully realize the potential of the Merdeka Curriculum. This study offers conceptual insights for the development of future educational policies that are more responsive to the demands of the 21st century while remaining relevant to both local and global contexts.